Altered physiological functions and ion currents in atrial fibroblasts from patients with chronic atrial fibrillation. Issue 2 (26th January 2016) - Poulet, Claire; Künzel, Stephan; Büttner, Edgar; Lindner, Diana; Westermann, Dirk; Ravens, Ursula
Abstract: The contribution of human atrial fibroblasts to cardiac physiology and pathophysiology is poorly understood. Fibroblasts may contribute to arrhythmogenesis through fibrosis, or by directly altering electrical activity in cardiomyocytes. The objective of our study was to uncover phenotypic differences between cells from patients in sinus rhythm (SR) and chronic atrial fibrillation (AF), with special emphasis on electrophysiological properties. We isolated fibroblasts from human right atrial tissue for patch‐clamp experiments, proliferation, migration, and differentiation assays, and gene expression profiling. In culture, proliferation and migration of AF fibroblasts were strongly impaired but differentiation into myofibroblasts was increased. This was associated with a higher number of AF fibroblasts expressing functional Nav1.5 channels. Strikingly Na + currents were considerably larger in AF cells. Blocking Na + channels in culture with tetrodotoxin did not affect proliferation, migration, or differentiation in neither SR nor AF cells. While freshly isolated fibroblasts showed mostly weak rectifier currents, fibroblasts in culture developed outward rectifier K + currents of similar amplitude between the SR and AF groups. Adding the K + channel blockers tetraethylammonium and 4‐aminopyridin in culture reduced current amplitude and inhibited proliferation in the SR group only. Analysis of gene expression revealed significant differences between SR and AF in genes encoding for ion channels, collagen, growth factors, connexins, and cadherins. In conclusion, this study shows that under AF conditions atrial fibroblasts undergo phenotypic changes that are revealed in culture. Future experiments should be performed in situ to understand the nature of those changes and whether they affect cardiac electrical activity. Abstract : This study investigated the effects of chronic atrial fibrillation (AF) on the phenotype of human atrial fibroblasts, with special emphasis on electrophysiological properties. Compared to control cells, cultured AF fibroblasts showed impaired proliferation and migration, increased differentiation, as well as larger inward rectifier K + currents and voltage‐gated Na + currents. While we did not find any evidence for the involvement of Na + currents in major fibroblast functions, our data establish a link between voltage‐gated K + currents and proliferation of control fibroblasts.